Spending behavior of UTAR undergraduate students - Lai, Yee Xiang; Ting, Siew Toong; Wong, Huey Ying (2022)
Identify the spending behavior of UTAR undergraduate students and the changes of online spending behavior in different categories. Investigate the factors (family income, price elasticity, peer influence and, financial literacy) that influence the spending behavior of UTAR undergraduate students. To investigate the changes of online spending behavior of UTAR undergraduate students before and after the pandemic in different categories such as leisure, ordering food from e-hailing apps, branded products, groceries, clothes, and health care products.